Modern rice varieties adoption to raise productivity: a case study of two districts in Bhutan (SAARC Journal of Agriculture, 2016)
Rice (Oryza sativa L.) is one of the main staple crops of Bhutan and is grown in all 20 districts of the country. Due to its key role in national food security, a number of development interventions like promotion of modern rice varieties is carried out. To assess the impact of such development interventions, this study investigated whether the farmers in two main rice growing districts, Punakha and Wangdue, have adopted the promoted rice varieties. Within a district, ten main rice growing geogs (administrative units) were chosen for the study. Representing the study area a questionnaire farming-household survey of 580 was carried out in 2014. The study found that the farming household level variety adoption rate was 68% and 62% in Wangdue and Punakha, respectively. The main modern varieties adopted by the surveyed farming households were IR-64, Khangma Maap, Bajo Maap, Bajo Kaap, No. 11 and IR- 20913. In terms of area coverage, 54.50% of the area in Wangdue was covered by improved varieties and that in Punakha was 56.71%. Among the adopted varieties, the most widely grown variety in both the districts was IR-64 that accounts for about 55% adoption. However, the least adopted variety was IR-20913 which stood at just 0.2% in Wangdue and 2% in Punakha. Yield increase due to improved varieties over local ones, 80% of households in Wangdue and 91% of households in Punakha reported achieving 25% and 33% increases together. In Wangdue 80% of the households reported yield increase and in Punakha it was 91%, which corresponded to 25% and 33% increases, respectively. This surveyed finding can be validated by crop-cut yield data which was greater than or equal to 26% yield increase, on an average, by improved varieties over local ones. In terms of farmers adoption rate of modern rice varieties and area covered by the modern varieties, the findings showed that there is a major impact of rice development interventions in Punakha-Wangdue valley to support food security of the farming households as well as for adding to the national food basket.SAARC J. Agri., 13(2): 34-49 (2015)